Penerapan Subak dalam Institusi Sosial Petani Transmigran Bali - Nurning Agusriyanti Naris (Universitas Negeri Makassar, 2022)
Balinese people live harmoniously with beliefs and culture that simultaneously. not only known for its beautiful beaches but also no less interesting is its agriculture. Subak is a traditional Balinese agricultural institution which is still being maintained. In general, many also interpret subak as an irrigation institution. Studies on subak in Bali have been written by several researchers both from within and outside the country. It is interesting how farmers still apply traditional agricultural institutions where now various government programs related to agriculture are implemented. Bali has proven that it can survive and cooperate with the local government to combine subak and farmer groups. This study wants to provide another description of how the implementation of subak is carried out elsewhere by farmers from Bali through the transmigration program. Without irrigation, the subak institution can still function as a farmer's living space. This research is reviewed from a sociology religious perspective using the ethnographic writing method through several field studies. This paper contributes to understanding Balinese farming communities who continue to maintain their beliefs and culture through a traditional institution called â€œsubakâ€.Â